Edgeworth Approximations in First Order Stochastic Difference Equations with Exogenous Variables - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 1982)
This article obtains the Edgeworth approximate distribution of the OLS estimator of the autoregressive parameter of a first-order stochastic difference equation with exogenous variables. The approximate distribution is compared with the exact distribution computed using the Imhof algorithm. Phillips' results on the pure autoregressive process are also revised.